1987
DOI: 10.1111/j.1432-1033.1987.tb10757.x
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of heat‐shock proteins and spontaneous synthesis of HSP70 during the life cycle of Blastocladiella emersonii

Abstract: The heat-shock response in Blustocludiellu emrrsonii is dependent on the developmental stage. Cells exposed to elevated temperatures at different stages of the life cycle (sporulation, germination or growth) show a differential synthesis of heat-shock proteins (hsps). Of a total of 22 polypeptides induced, particular subsets of hsps appear in each phase, demonstrating a non-coordinate heat-shock gene expression. In contrast, heat-shock-related proteins (hsp76, hsp70, hsp39a) are spontaneously expressed at a hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0
4

Year Published

1987
1987
2010
2010

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 40 publications
3
13
0
4
Order By: Relevance
“…Among the upregulated genes, only 34 of them were induced in both stages of development. These results suggest a developmental control of the heat shock response in B. emersonii, in agreement with previous data obtained through two-dimensional gel electrophoresis analysis of 35 S-labeled protein extracts that showed that different sets of heat shock proteins were synthesized in cells exposed to high temperature according to the stage of the fungus life cycle (8). Table 3 shows the genes with matches in the GenBank and/or Swiss Prot databases and classified as upregulated (threefold or more) in response to heat shock during sporulation (S) and germination (G) stages.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…Among the upregulated genes, only 34 of them were induced in both stages of development. These results suggest a developmental control of the heat shock response in B. emersonii, in agreement with previous data obtained through two-dimensional gel electrophoresis analysis of 35 S-labeled protein extracts that showed that different sets of heat shock proteins were synthesized in cells exposed to high temperature according to the stage of the fungus life cycle (8). Table 3 shows the genes with matches in the GenBank and/or Swiss Prot databases and classified as upregulated (threefold or more) in response to heat shock during sporulation (S) and germination (G) stages.…”
Section: Resultssupporting
confidence: 81%
“…The heat shock response has been previously analyzed in B. emersonii and shown to be developmentally regulated, with different subsets of heat shock proteins (Hsps) being synthesized in response to heat stress during sporulation, germination, and vegetative growth (8). In addition, differences have been observed in the degree of induction of B. emersonii heat shock genes, depending on the stage of the fungus life cycle (24,47,57).…”
mentioning
confidence: 99%
“…hsp mRNA was also not detected in the zoospores of Blastocladiella emersonii, despite the fact that some other mRNA species were apparently stored in the spores [24,25]. The same result was obtained in Leptosphaeria maculans [26].…”
Section: Dormant Sporessupporting
confidence: 66%
“…In B. emersonii, synthesis of various HSPs was induced by heat shock during the germination of spores: the induction of HSP24 appeared to be speci¢c for this stage and occurred only 45 min after germination begins [24]. The highest constitutive amounts of hsc70 and hsc80 transcripts in L. maculans were found in germinating spores, a state which might be associated with stress, because Leptosphaeria's invasion of the host plant takes place during germination [26].…”
Section: Germinating Sporesmentioning
confidence: 99%
“…Studies on sHsp regulation in dormancies of different organisms revealed heterogenous patterns (Bonato et al 1987;Yocum et al 1991;Denlinger et al 1992;Liang et al 1997a;Yocum et al 1998;Tammariello et al 1999;Cherkasova et al 2000;Goto and Kimura 2004;Rinehart et al 2007;Gkouvitsas et al 2008), indicating a diverse array of functions. An essential upregulation of shsp has been suggested for cold hardiness in the flesh fly Sarcophaga crassipalpis (Rinehart et al 2007).…”
Section: Discussionmentioning
confidence: 99%